Comparing different strategies of minimising embodied carbon in concrete floors. (15th April 2022) - Jayasinghe, Amila; Orr, John; Hawkins, Will; Ibell, Tim; Boshoff, William P.
Abstract: The present climate emergency demands the construction industry to minimise the carbon footprint of concrete buildings. In this paper, the potential different optimisation strategies to reduce 'cradle-to-gate' embodied carbon of concrete floors which require different levels of modifications to the conventional design and construction practice were compared. The embodied carbon savings possible from parametrically optimising slab depth and grade of concrete, post-tensioning, considering alternative conventional slab types, and adopting novel thin shell floor systems were quantified for a range of spans. Compared to reinforced concrete flat slabs designed for conventional span/depth ratios, minimising slab depths and considering lower grades of concrete can reduce embodied carbon of flat slabs up to 12%, only with changes to the design methods. By adopting other conventional alternatives available in the present market, post-tensioning can save embodied carbon up to 23% but two-way slabs on beams and hollow-core slabs can save up to 36%. Much higher carbon reductions up to 65% are possible with novel construction methods of thin shell floors that transfer loads through membrane action rather than bending. Hence, the construction industry should approach shape optimised floor construction forms in future while adopting parametric design and considering conventional alternatives in the present to minimise carbon emissions. Graphical abstract: Image 1 Highlights: Optimisation strategies with different changes to traditional practice are compared. Parametric design of depth and grade of concrete in flat slabs cut up to 12% carbon. Selecting the design from conventional slab alternatives can save carbon up to 36%. Floor systems that transfer loads through compression arches reduce carbon by 65%.